Studies toward the Synthesis of Hepta-peri-heptabenzo-[7]circulene - Yang, Xuejin; Miao, Qian (Synlett, 2016)
In this letter we report the synthesis and characterization of two new heptagon-embedded nonplanar π-conjugated molecules, which can be regarded as synthetic precursors of hepta-peri-heptabenzo-[7]circulene, an interesting but unknown polycyclic arene with negative curvature.
Keywords: polycyclic arenes; negatively curved π molecules; oxidative cyclodehydrogenation